Analisis Parameter Fisik Kualitas Air pada Depot Air Minum Isi Ulang (DAMIU) DI Kecamatan Tanjung Redeb - Yanti, Nuri; Wardhani, Pratiwi Sri; Mislan, Mislan; Munir, Rahmawati; Hamdani, Dadan (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2023)
DAMIU (Refill Drinking Water Depot) is an individual or group business that manages refill drinking water for public consumption directly filled on the spot and not in packaged form, this water must meet the standardization of drinking water quality requirements with one of its parameters, namely physical parameters that do not directly related to health, namely temperature, pH, total dissolved solids and electrical conductivity. This research was conducted to determine the quality of refill drinking water in Tanjung Redeb Subdistrict, whether it complies with the Regulation of the Minister of Health of the Republic of Indonesia Number 492/MENKES/PER/IV/2010 concerning drinking water quality requirements and to determine the effect of the duration of water storage on drinking water quality with parameters physical. This research was conducted in Tanjung Redeb District, Berau Regency and was carried out with 2 different water sources, namely drilled wells and PDAM. Water quality is measured using a TDS meter. Based on the research that has been done, the results of measuring the quality of refill drinking water in Tanjung Redeb District, Berau Regency, namely the water quality meets the standardization of the Regulation of the Minister of Health of the Republic of Indonesia Number 492/MENKES/PER/IV/2010 concerning drinking water quality requirements and the result is that the storage time for 15 days had an effect on changes in the values ​​of the parameters pH, TDS and DHL and even though they were stored for 15 days the quality still met drinking water quality standards while the temperature parameter had no effect.